Itupale Ewi Ajemokuu Laarin awon Egba ati Ijebu (A Critical Appraisal of Funeral Dirges among the Egba and Ijebu) - Kareem, Mudasiru Abayomi (2015)
The study examined dirges among the Egba and Ijebu of Ogun State. It analysed their contents and examined the use of language in the genre, with a view to highlighting their aesthetic qualities and thematic preoccupations.